2017
DOI: 10.1002/andp.201700335
|View full text |Cite
|
Sign up to set email alerts
|

Single Metal Ohmic and Rectifying Contacts to ZnO Nanowires: A Defect Based Approach

Abstract: Ohmic and rectifying metal contacts to semiconductor nanowires are integral to electronic device structures and typically require different metals and different process techniques to form. Here we show how a noble metal ion beam of Pt commonly used to pattern conducting contacts in electron microscopes can form both ohmic and Schottky/blocking contacts on ZnO nanowires by controlling native point defects at the intimate metal-semiconductor interface. Spatially-resolved cathodoluminescence spectroscopy on a nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the following sections, we will sum up the electronic behavior of Ga For the highest metal work-function, [128,129] Pt has been widely employed in Schottky devices. [130][131][132] In 2013, Sasaki et al [127] deposited a Pt circular electrode with a diameter of 100 µm on (010) β -Ga 2 O 3 single crystal substrate with a thickness of 600 µm to fabricate SBD. The SBH between Pt and β -Ga 2 O 3 was 1.3-1.5 eV, which was larger than those of Pt/6 H-SiC (1.06-1.33 eV), [133] Pt/4H-SiC (1.39 eV), [134] and Pt/GaN (1.11-1.27 eV), [135] the catastrophic breakdown occurred at the cathode edge and V br was 150 V, and the ideality factor was 1.04-1.06 close to unity.…”
Section: Schottky Barrier Diodementioning
confidence: 99%
“…In the following sections, we will sum up the electronic behavior of Ga For the highest metal work-function, [128,129] Pt has been widely employed in Schottky devices. [130][131][132] In 2013, Sasaki et al [127] deposited a Pt circular electrode with a diameter of 100 µm on (010) β -Ga 2 O 3 single crystal substrate with a thickness of 600 µm to fabricate SBD. The SBH between Pt and β -Ga 2 O 3 was 1.3-1.5 eV, which was larger than those of Pt/6 H-SiC (1.06-1.33 eV), [133] Pt/4H-SiC (1.39 eV), [134] and Pt/GaN (1.11-1.27 eV), [135] the catastrophic breakdown occurred at the cathode edge and V br was 150 V, and the ideality factor was 1.04-1.06 close to unity.…”
Section: Schottky Barrier Diodementioning
confidence: 99%
“…In this respect, ZnONWs have been widely studied because of their excellent mechanical flexibility, optical and electrical properties, and good environmental adaptability. Many techniques have been used to prepare ZnONWs, including physical techniques, such as vapor–liquid–solid (VLS) [ 4 ], chemical vapor deposition (CVD) [ 5 ], pulsed laser deposition (PLD) methods [ 6 ], and chemical techniques by hydrothermal [ 7 ] and chemical bath deposition (CBD) methods [ 8 ]. Nonetheless, the physical techniques usually require a lot of energy.…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility of ZnO enables bio-implanted nanogenerators [14] and degenerately-doped ZnO enables plasmonic coupling of photons with electronics [4]. Recent studies have shown that native point defects are present in the “bulk” of ZnO nanowires and not just on their surfaces [15,16]. These defects inside nanowires and at their metal junctions can dominate the electrical contact properties, yet they can be moved by applied electric fields [17] or removed by ion beam techniques [18], Since defect segregation to free surfaces and interfaces is common among semiconductors [19], and its effect is magnified in semiconductor nanostructures, these results can have more general significance.…”
Section: Introductionmentioning
confidence: 99%